Mapping an Atlantic world circa 1500 - Metcalf, Alida C., 1954- (Johns Hopkins University Press, 2020)
"The year 1500, Metcalf argues, was a turning point in Europeans' understanding of their world in relation to the Atlantic Ocean. In the sixteenth century, cartographers began to conceptualize-and present to the public-an interconnected Atlantic World that was open and navigable, in contrast with the mysterious ocean that had blocked off the Western hemisphere before Columbus. The author contends that early modern cartographers were significant agents in the intellectual history of the Atlantic World"--